Infrared Lamp Therapy on Episiotomy Wound during Postpartum Period: An Integrative Review - Hongranai, Sineenat; Limprasert, Dutchanee (Nursing Science Journal of Thailand, 2022)
Purpose: An integrative review of the literature to compare the infrared lamp therapy on episiotomy wound and non-infrared lamp therapy during the postpartum period whether they affected to level of perineal wound pain and wound healing. Design: The documents were searched from electronic databases including published ScienceDirect, Cochrane, OCLC, HighWire Press, CINAHL, PubMed, Google Scholar and ThaiJO between January 2010 and December 2020. The criterion for selection of the literature followed the PICOT framework. Research findings: The searching and selection came up with seven-studies; including one experimental research and six quasi-experimental researches. Conclusion and recommendations: The results of these reviews indicated that, compared to those who did not received infrared lamp therapy group, the mothers who received the therapy showed significantly decreased episiotomy wound pain score within 3 days postpartum, and significant improvement in episiotomy wound healing within 4 days postpartum. The finding suggested that the application of infrared lamp therapy should be encouraged for reducing episiotomy wound pain and wound healing during postpartum.